Neonatal Effects of Substance Abuse during Pregnancy - Reza Saeidi; Ehsan Mosa Farkhani; Maryam Saeidi; Shokufeh Izadi; Maryam Ziadi lotfabadi (Mashhad University of Medical Sciences, 2016)
Drug abuse in pregnancy is not uncommon, and the use of illicit opioids during pregnancy is associated with an increased risk of adverse outcomes. The aim of the study was to assess neonatal outcome of pregnancy with maternal addiction. Materials and Methods:   In this cohort study we assessed 100 pregnant women 15 -49 years old. To identify drug exposure was used self- questionnaire (Self-Report). Data on pregnancies complicated by illicit drug abuse (n = 50) were collected during a 2-year period (2014 - 2016) at Hospitals affiliated to Mashhad University of medical sciences. Data on the type of drug, course of gestation and labor, and on neonatal complications outcome were considered. Medical records on all non-dependence pregnancies during the study period were used as a non-exposed group (n = 50).To control possible confounding factor was used of multiple logistic regression model. Results: our results showed The risk of various congenital anomalies was 5-fold in the group of children born to addicted mothers (RR = 5.65, 95% CI: 0.27-114.7). Also RDS (RR=5.1, 95% CI: 1.16-22.3), meconial amniotic fluid (RR=2.26, 95% CI: 0.21-24.1), NICU admission (RR=3.07, 95% CI: 1.93-4.88), neonatal seizure (RR=5.38, 95%CI: 1.97-14.64), neonatal hypoglycemia (RR=2.26, 95% CI: 0.60-8.54) were significantly more common in the group of pregnant addicts. Conclusion: Addiction pregnancies must be considered as high-risk pregnancies according to perinatal outcome. We should prepare Appropriate obstetric and neonatal care in these pregnancies.